The Impact of COVID-19 Pandemic on Psychiatric Emergencies in Two Different Settings: Emergency Room and Community Mental Health Service - Di Lorenzo, Rosaria; Pinelli, Margherita; Bertani, Davide; Cutino, Anna; Dragone, Diego; Elia, Claudia; Farina, Riccardo; Fiore, Gianluca; Luisi, Filippa; Panico, Sofia; Valeo, Laura; Rovesti, Sergio; et al. (Frontiers in Psychiatry, 2022)
Background The SARS-CoV-2 pandemic caused a public health emergency with profound consequences on physical and mental health of individuals. Emergency Rooms (ER) and Community Mental Health Services (CMHS) played a key role in the management of psychiatric emergencies during the pandemic. The purpose of the study was to evaluate urgent psychiatric consultations (UPCs) in the ERs of the General Hospitals and in the CMHS of a Northern Italian town during the pandemic period. Methods This monocentric observational study collected UPCs carried out in ER from 01/03/2020 to 28/02/2021 (the so called “COVID-19 period”) and the demographic and clinical characteristics of patients who required UPCs in the 12-months period, comparing these data with those collected from 01/03/2019 to 29/02/2020 (the so called “pre-COVID-19 period”). The same variables were collected for UPCs carried out in CMHS from 01/03/2020 to 31/01/2021 and compared with those collected from 01/03/2019 to 31/01/2020. The data, were statistically analyzed through STATA 12-2011. Results In ER, we reported a 24% reduction in UPCs during the COVID-19 period (n = 909) in comparison with the pre-COVID-19 period (n = 1,194). Differently, we observed an increase of 4% in UPCs carried out in CMHS during the COVID-19 period (n = 1,214) in comparison with the previous period (n = 1,162). We observed an increase of UPCs in ER required by people who lived in psychiatric facilities or with disability pension whereas more UPCs in CMHS were required by older people or those living in other institutions compared to the previous period. In the COVID-19 period, the most frequent reasons for UPCs in ER were aggressiveness, socio-environmental maladjustment and psychiatric symptoms in organic disorders whereas in CMHS we reported an increase of UPCs for control of psychopharmacology therapy and mixed state/mania. Conclusion In light of our findings, we conclude that the most vulnerable people required more frequent attention and care in both ER and CMHS during pandemic, which disrupted individuals’ ability to adapt and induced many stressful reactive symptoms. In order to reduce the impact of the COVID-19 pandemic on mental health, psychological support interventions for the general population should be implemented, having particular regard for more psychologically fragile people.